Oral reading fluency with peer-assisted reading via telecollaboration. Issue 3 (1st September 2016) - Lin, Yi-Ti
ABSTRACT: The purpose of this research was to investigate the effects of peer-assisted reading on oral reading fluency of English as a foreign language (EFL) learners via telecollaboration. A telecollaboration was set up which compensated for the lack of natural and authentic input in an EFL context and enabled Taiwanese elementary school students to work and interact with Australian primary school students. With peer-assisted reading, natural speech input was made available, and the EFL learners were able to practice oral reading fluency with accuracy, appropriate speed, and expression. An English/Chinese bilingual story book was used for the telecollaboration and participants from both sides took turns being the helper and the helped in modeling and assisting their peers to read the story book. Recordings of the text by the EFL participants before and after the telecollaboration were used as data of analysis. The pretests and the posttests of oral reading fluency, in terms of accuracy, speed, and expression, were compared using the Wilcoxon Signed Ranks Test. The results revealed significant improvements in the three dimensions and the findings suggested that peer-assisted reading with native speakers via telecollaboration was an effective way to improve EFL learners' oral reading fluency.